Utilization of weeds as instructional materials in high school science - Garcia, Manuel B. 1943- ([S.l s.n.], 1974)
This paper aimed to develop a teaching unit on weeds that is intended particularly for high school freshman and/or sophomore students. Such teaching unit attempts to: (1) include selected learning activities with particular emphasis on the ecology of weeds; (2) provide the students with opportunities to equip themselves with basic information about weeds as well as to develop in them certain basic science skills; and (3) make both the science teacher and students realize the ecological importance of weeds.